Developing a reduced order model from structural kinematic measurements of a flexible finite span wing in stall flutter. (May 2017) - Culler, Ethan C.E.; Fagley, Casey; Seidel, Jürgen; McLaughlin, Thomas E.; Farnsworth, John A.N.
Abstract: Experiments were conducted on a flexible, finite-span cyber–physical wing model in the wind tunnel to study the structural kinematics for a wing undergoing stall flutter. The wing model was designed to be weak in torsion and stiff in bending to exhibit stall flutter oscillations. The physical deformation of the wing surface was mapped at 38%, 58%, 78%, and 98% span using a stereo vision motion tracking system. From these measurements, the wing motion is decomposed and shown to consist of a principally torsional (pitching) oscillation consistent with the first mode for a cantilevered beam in free vibration. A two equation empirical model of the wing motion was then developed and compared to the measured stall flutter motion.